Acute Hepatitis C: Clinical Aspects, Diagnosis, and Outcome of Acute HCV Infection - Fabris, P.; Fleming, V. M.; Giordani, M. T.; Barnes, E. (Current Pharmaceutical Design, 2008)
Acute hepatitis C virus (HCV) infection is often a clinically silent infection, and is therefore rarely detected. A high index of clinical suspicion in addition to careful serological and virological assessment is required to identify the disease, and to determine the eventual clinical outcome after primary infection; the minority of acutely infected individuals spontaneously control viremia in long term whilst the majority become persistently infected. Here, we describe the clinical presentation of acute HCV infection and the patterns of viremia and liver alanine transaminase levels (ALT) observed. We discuss the serological and virological assessment and potential pitfalls in accurately diagnosing acute HCV. Good prospective studies that identify host and virological factors that determine clinical symptoms and disease outcome are difficult to perform due to the asymptomatic nature of infection, but some progress has been made in this field. Host factors including gender, age at time of infection, prior resolution of infection, symptomatic infection and host immune responses, and viral factors such as the nature of the infecting quasispecies and more speculatively viral genotype, are some features that have been correlated with disease outcome. In spite of this, on an individual patient level, it is currently not possible to predict those that will resolve infection. Identifying, in detail therefore, those factors that are responsible for viral control remains an important research goal not only to aid clinical management but also to develop effective treatment and vaccination strategies.
Keywords: viral